Literasi Digital Guru di Era Kurikulum Merdeka: Tantangan, Kesiapan, dan Implikasi terhadap Kualitas Pembelajaran - Rizqi, Ascosenda Ika; Lutfiana, Rose Fitria; Nanda, Hanjar Ikrima (CV. Global Cendekia Inti, 2025)
Teacher digital literacy has become a key competency in supporting the successful implementation of the Kurikulum Merdeka (Independent Curriculum) in Indonesia. This study aims to analyse the challenges, readiness, and implications of teachers’ digital literacy for the quality of learning. Employing a systematic literature review, the study synthesises findings from national and international research published between 2017 and 2025. The review reveals that teachers continue to face significant challenges, including limited technological infrastructure, generational gaps in digital proficiency, and insufficient institutional support. Teachers’ readiness varies widely, shaped by professional experience, access to digital training, and engagement in professional learning communities. The findings indicate that strong digital literacy contributes positively to learning quality by enabling interactive, innovative, and student-centred pedagogical practices aligned with 21st-century competencies. However, disparities in access—particularly in 3T (frontier, outermost, and underdeveloped) regions—hinder equitable implementation. Strengthening teachers’ digital literacy therefore requires coordinated efforts across individual, institutional, and governmental levels. Enhancing practical training, improving school-level digital infrastructure, expanding professional learning networks, and promoting inclusive digital policies are essential to ensure that Kurikulum Merdeka can be implemented effectively and equitably throughout Indonesia.